Essentials of Musculoskeletal Imaging - Vinall, Maria (MD Conference Express, 2015)
This article reviews the conventional magnetic resonance imaging features of common, sports-related shoulder pathology, as well as of MRI of a normal ACL graft reconstruction and a graft failure. Also discussed are the indications and technique for shoulder magnetic resonance arthrography for evaluating the shoulder labroligamentous complex.